THE EFFECTIVENESS OFTHE INSTRUCTIONAL MODEL OF PLAYING TO INCREASE THE PHYSICAL FITNESS OF THE LOWER GRADE OF ELEMENTARY SCHOOL STUDENTS - Sukarmin, Yustinus (Universitas Negeri Semarang, 2013)
This research is inspired by the problem on the low physical fitness of the elementary school students due to the development of technology and they are not really interested to follow the physical education subject. The aim of this study is to find the effectiveness of instructional model of playing as the way to increase the elementary school studentsÃ¢â‚¬â„¢low grade of physical fitness. This research uses Research and Development design, which was established by Borg and Gall. The effectiveness test was conducted to 40 students of Adisucipto 1 elementary school. The data collection method used was: (1) observation guide and (2) physical fitness tests. The descriptive quantitative analysis technique was used to analyse the data using a product moment correlation statistical formulae. The resultsÃ‚Â of this research reveal that: (1) there has been a significant change from cycle I to cycle II for all aspects measured, such as enthusiasm, excitement, discipline, and totality from Average to Good, (2) a change in the number of students who are fit and unfit inÃ‚Â cycle I to cycle II, the number of students who are in the fit category grew in 10 % and students who are not in the fit category decreased in10 %, and (3) the result of the correlation between the data observation result (X) and the result of the physical fitness test data (Y) or rXY = 0.904, is greater than the r value table = 0.312. Thus, there is a significant correlation between the result of the observation and physical fitness test result.